The intelligent library system creating the ultimate patron experience
This multimedia presentation review the new RFID technology by Checkpoint System Inc. where library can apply latest technology in providing services and free stuff from time-consuming tasks. Watch the demo video, browse for product brochure, visit the ILS website and view the contact details.